2018
DOI: 10.1016/j.aop.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Duality and topology

Abstract: Mappings between models may be obtained by unitary transformations with preservation of the spectra but in general a change in the states. Noncanonical transformations in general also change the statistics of the operators involved. In these cases one may expect a change of topological properties as a consequence of the mapping. Here we consider some dualities resulting from mappings, by systematically using a Majorana fermion representation of spin and fermionic problems. We focus on the change of topological… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…where q(k) = −2J cos k − µ + 2i∆ sin k. The winding number can be calculated using the definition [47] w…”
Section: Mathematically For Our Model Hamiltonian Berry Connection Is...mentioning
confidence: 99%
See 2 more Smart Citations
“…where q(k) = −2J cos k − µ + 2i∆ sin k. The winding number can be calculated using the definition [47] w…”
Section: Mathematically For Our Model Hamiltonian Berry Connection Is...mentioning
confidence: 99%
“…Topological properties can also be determined by the complex analysis of the parameter space [25,26]. Topological phase transition points are considered as the singularity points in the parameter space.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple quenches have been studied in only several works [100,101,112]. In [100] it has been shown that for quenches of a type A→B→A, where A and B label different equilibrium phases, that DQPTs is by no means inevitable and can be tuned away by choosing the second quench time T appropriately.…”
Section: Introductionmentioning
confidence: 99%